Analisis Model Think Pair Share Untuk Meningkatkan Keterampilan Menulis Puisi Siswa Sekolah Dasar - Dian Lestari; Ibnu Muthi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the effectiveness of implementing the Think Pair Share (TPS) learning model in improving elementry school students writing skills. This research was carried out using a method in the form of a literature study, namely Literature review.. Data obtained was the result of journal literature of scientific articles related to the Think Pair Share (TPS) learning model in elementry school students poetry writing skills, so in this research, researchers did not conduct direct research in the field. The research can streng then the argument that the Think Pair Share (TPS) learning model is capable of developing students skills in writing poetry in elementry schools and is suitable for use in the process of learning and teaching activities.